Determination of New Zealand tertiary institution e-learning capability: An application of an e-learning maturity model - Stephen Marshall (Flexible Learning Association of New Zealand, 2012)
A significant challenge facing most tertiary institutions is identifying organisational strategic and operational priorities for investment in e-learning capability-in short, containing the rising cost of e-learning infrastructure while maximising the educational outcomes for students. This project is engaging in a detailed e-learning capability determination exercise over a number of New Zealand Tertiary Education Organisations (TEOs). This will assess their current strategic and operational capability for delivering and maintaining e-learning in an educationally effective but also organisationally effective manner. This process is intended to validate a framework for conducting such capability determinations and provide a documented standard methodology for determining e-learning strengths and weaknesses institutionally and by sector.